Biogas in Science Education: A Systematic Literature Review and Bibliometric Mapping of Trends, Challenges, and HOTS Integration (2015–2024) - Rinda Fitri Handayani; Rendy Wikrama Wardana; Afrizal Mayub; Fitri April Yanti; Euis Nursaadah; Suzieleez Syrene Abdul Rahim; Noorzana Khamis (Jurnal Pendidikan MIPA, 2026)
Biogas is a renewable, environmentally friendly energy source with significant potential for science education, offering an alternative to the global fossil fuel crisis. This study aims to provide a brief overview of research trends, publication contributions, methodologies used, thematic coverage, and teaching integration in the biogas-based science education literature. This study is a Systematic Literature Review (SLR) with bibliometric analysis, supported by Publish or Perish and VOSviewer, including 720 selected articles from the period 2015 to 2024. The results show that, since 2020, publications related to biogas have increased significantly, with three main research focuses: the use of organic waste for renewable energy development; the application of biogas as an alternative global energy source through technological innovation; and its integration into HOTS learning and education. The majority of the publications come from reputable international journals such as Energies and Sustainability. Case studies and reviews remain the dominant research protocols, while empirical designs such as experiments and surveys are still relatively rare, leaving room for more applied follow-up studies. This review also finds that the application of biogas in science education can support the development of Higher Order Thinking Skills (HOTS). However, this application remains limited in the existing literature. Therefore, the findings highlight the need for further empirical research to more deeply explore the potential of biogas for science education and HOTS development. This study provides new insights that the biogas literature has not fully integrated practical applications for HOTS development, thus requiring further creative and applied research to address this gap. Keywords: alternative energy, biogas, environmentally friendly, HOTS, science education.